Pulsed dye laser treatment of vascular malformation, 10 years follow up - Crivaro, Paula; Bollea Garlatti, María Luz; Ferrario, Damián; Mazzuoccolo, Luis Daniel (Revista del Hospital Italiano de Buenos Aires, 2018)
Port wine stains are a type of vascular malformation that affects 0.3% to 0.5% of the population. They are present from birth as erythematous macules or plaques on the skin or mucous membranes. Without treatment, these lesions tend to darken with age, becoming reddish or purple and may develop nodular thickening or an associated pyogenic granuloma. Laser treatments might provide an improvement by selective destruction of the vasculature. A variety of selective vascular lásers may be employed, with the pulsed dye laser as the gold standard treatment. Better results are obtained when the treatment is established early